Mapping postcommunist cultures : Russia and Ukraine in the context of globalization - Chernetsky, Vitaly (McGill-Queen's University Press, 2007)
Drawing on the discourses of postmodernism, postcolonialism, and globalization, Vitaly Chernetsky maps out the new cultural developments in literature, architecture, painting, film, and performance art emerging in Russia and Ukraine, the two largest successor states to the Soviet Union, situating these phenomena in a greater global context.
Keywords: Russian literature -- 20th century -- History and criticism.; Ukrainian literature -- 20th century -- History and criticism.; Postmodernism (Literature) -- Russia (Federation); Postmodernism (Literature) -- Ukraine.; Littérature russe -- 20e siècle -- Histoire et critique.; Littérature ukrainienne -- 20e siècle -- Histoire et critique.; Postmodernisme (Littérature) -- Russie.; Postmodernisme (Littérature) -- Ukraine.; LITERARY CRITICISM -- Russian & Former Soviet Union.; POLITICAL SCIENCE -- International Relations -- General.; Postmodernism (Literature); Russian literature; Ukrainian literature; Russia (Federation); Ukraine; 1900-1999; Electronic books.; Criticism, interpretation, etc.